Evaluation of N Efficiency Using Prilled Urea and Urea Super Granules in T. Aman Rice (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the Experimental field of Department of Agronomy, Bangladesh Agricultural University, Mymensingh, during June to December 2007 to evaluate the nitrogen use efficiency of transplant aman rice using prilled urea (PU) and urea super granule (USG). Three rice varieties (BR11, BRRI dhan30 and BRRI dhan39) were compared at three doses of nitrogen, i.e., PU@125 kg N ha-1, USG @170 kg N ha-1 and USG @ 70 kg N ha-1 in a Randomized Complete Block (RCB) design with three replications. USG each weighing 1 g and 2.6 g were placed manually at the depth of 8-10 cm in the middle of four hills in alternate rows at 12 days after transplanting and PU applied in split applications. The rice var. BR11 at USG @70 kg N ha-1 has produced the maximum grain yield (4.75 t ha-1) which was statistically identical to BRRI dhan30 at USG @ 70 kg N ha-1 (1 g pellet-1). The highest nitrogen use efficiency, partial factor productivity and marginal rate of return (1966%) were recorded from the treatment of BR11 at USG @ 70 kg N ha-1.Bangladesh Agron. J. 2015, 18(1): 59-63